Decision support system for medical pathology recognition - Писарчук, Олексій Олександрович; Міронов, Ю. Г. (Science-based technologies, 2021)
Given article considers the problem of automation of chromosome pathology recognition. Overview of existing publications in adjacent topics has shown the need for further research due to the scientific relevance and lack of groundwork. The application domain has been considered - both theoretical aspects of pathology recognition automation and the chromosome pathology diagnostics process itself. Classification of main chromosome abnormalities has been performed. A formal algorithm has been derived from the aforementioned application domain analysis. The algorithm version provided in given publication is a high-level draft and will be extended. Along with the algorithm, requirements to the prototype software and the prototype software itself have been designed. It should accept karyogram image as an input and return information about chromosome anomaly as an output. Software has been implemented on Python programing language using OpenCV image processing library. Prototype has been implemented as a program library, allowing to use it in different contexts. For example, it is possible to use it via terminal or design a Web API wrapper around it. Prototype of a decision support system for chromosome pathology recognition is currently capable of detecting quantity chromosome abnormalities. Results obtained from given paper prove the possibility of designing full-powered decision support system for chromosome pathology recognition automation and allow to focus on extending and improving functionality of each distinct step of the basic algorithm, allowing to cover more chromosome abnormality types